Menumbuhkan jiwa kewirausahaan berbasis kearifan lokal melalui pelatihan usaha batik tradisional: Studi kasus Workshop Batik Karawang - Sulaeman, Eman; Angelina, Nabilla Puteri; Oktaviani, Anggi; Ananda, Elfrida Putri (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2022)
This study aims to find out how to grow an entrepreneurial spirit based on local wisdom, find out how to train, improve the ability of traditional batik business, and find out how to improve mental competitiveness with competitors. using a research design with qualitative methods involving the case study Workshop Batik Karawang. Entrepreneurship based on local wisdom is an innovation to move forward without destroying the social fabric of society. This case study is on the Workshop Batik Karawang which is assisted by the Office of Cooperatives and Small and Medium Enterprises in Karawang Regency, one of the innovations is creating healthy cooperatives and pioneering batik villages.